Predicting Bankruptcy Using Altman's Z-Score And Zmijewski Models: Memprediksi Kebangkrutan Menggunakan Model Z-Score dan Zmijewski Altman - Yayu Kusdiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2023)
Oil and natural gas (oil and gas) are strategic natural resources and have an important role in national development. The need for oil and gas is expected to continue to increase in line with economic and population growth. Therefore, oil and gas business activities must be managed as well as possible to meet current and future supplies. Financial crises (financial distress) can occur in various companies and can be a signal of bankruptcy that the company may experience. The purpose of this study is to determine the bankruptcy prediction of Sub-Oil and Gas companies in Indonesia that are listed on the IDX in 2017 – 2020 using Altman's Z – score and Zmijewski models. The Altman Z-Score in predicting bankruptcy has a low accuracy rate of 22.72% with an error of 56.82%, while companies that are in a critical condition or gray area are not included in the calculation of the accuracy or type of error, due to the gray area cannot be determined whether the company is bankrupt or healthy, in other terms, namely the gray area. The Zmijewski in predicting bankruptcy is more accurate than the Altman Z-Score, which is 63.63% with a type error of 36.37%.